Approximate calculation of triboelectric charge density (σ) of nanoscale contact electrification. Issue 183 (2nd September 2017) - Ha, J.; Kim, S. M.; Kim, J.-B.
ABSTRACT: We have analytically approximated the triboelectric charge densities generated by triboelectrification reaching equilibrium over time in contact-mode TENG. It is assumed that the surface density of states (SDOS), Ns ( E ) is constant. The amount of electron transfer at the interface is estimated by calculating the change in vacuum energy level due to the charge density induced in the upper metal electrode and the lower metal electrode within the nanoscale separation range. Numerical results show that Ns ( E ) and work function difference are dominant compared to dielectric constant (material property) and dielectric thickness (structure parameter).